Dynamics of Self-Optimisation : An Introduction - Röcke, Anja; Nehring, Daniel; Salmenniemi, Suvi (Cologne GESIS, Leibniz Inst for the Social Sciences, 2025)
»Dynamiken der Selbstoptimierung: Eine Einführung«. This introduction
explores the increasing pervasiveness of discourses and practices of selfoptimisation
in present-day societies. These are evident in activities such as
self-tracking, fitness training, cosmetic surgery, neuroenhancement, or the
consumption of nutritional supplements. The growing appeal and diffusion
of these various practices testifies to the overall cultural attraction of self-optimisation,
which is a multifaceted phenomenon. Against the dominant interpretation
of self-optimisation as mainly driven by the logic of maximisation
and growth, we argue that it can also be about minimalism or balance. At the
same time, self-optimisation is strongly connected to dynamics of power and
social inequality, potentially reinforcing existing social inequalities and creating
new forms of domination and control. The paper starts by charting the
existing research and theoretical approaches to self-optimisation, presents
the contributions to the special issue, addresses a set of key domains of selfoptimisation
(therapeutic culture, health and well-being, digital technologies,
work, and economy), and finally draws conclusions and suggests some
avenues for future research.